Micromechanical evaluation of interfacial shear strength of carbon/epoxy composites using the microbond method - Willard, Bethany (Kansas State University, 2013)
Carbon fiber reinforced composites (CFRP’s) are a mainstay in many industries, including the aerospace industry. When composite components are damaged on an aircraft, they are typically repaired with a composite patch that is placed over the damaged material and cured into the existing composite material. This curing process involves knowledge of the curing time necessary to sufficiently cure the patch. The inexact nature of curing composites on aircraft causes a significant waste of time and material when patches are unnecessarily redone. Knowing how differences in cure cycle affect the strength of the final material could reduce this waste. That is the focus of this research. In this research, the interfacial shear strength (IFSS) of carbon fiber/epoxy composites was investigated to determine how changes in cure cycle affect the overall material strength. IFSS is a measure of the strength of the bond between the two materials. To measure this, the microbond method was used. In this method, a drop of epoxy is applied to a single carbon fiber. The specimen is cured and the droplet is sheared from the fiber. The force required to debond the droplet is recorded and the data is analyzed. The IFSS of AS4/Epon828, T650/Epon828, and T650/Cycom 5320-1 composites were evaluated. For the former two material systems, a cure cycle with two steps was chosen based on research from others and then was systematically varied. The final cure time was changed to determine how that parameter affected the IFSS. It was found that as the final cure time increased, so did the IFSS and level of cure achieved by the composite to a point. Once the composite reached its fully cured state, increasing the final cure time did not noticeably increase the IFSS. For the latter material system (T650/Cycom 5320-1), the two cure cycles recommended by the manufacturer were tested. These had different initial cure steps and identical final cure steps. Although both cure cycles caused high IFSS, the cycle with the higher initial temperature, but shorter initial cure time achieved a higher level of cure than that with a longer time, but shorter temperature.
Keywords: Microbond; Carbon fiber; Interfacial shear strength; Composite; Aerospace Engineering (0538); Materials Science (0794); Mechanical Engineering (0548)